Automatic space resection using a constrained relational matching - Dal Poz, Aluir Porfírio [UNESP]; Tommaselli, Antonio Maria Garcia [UNESP] (My University, 2000)
Image orientation is a basic problem in Digital Photogrammetry. While interior and relative orientations have been successfully automated, the absolute orientation (or space resection) continues to be an important topic for research. An approach has been developed to automate the absolute orientation based on relational matching and a heuristic that uses the analytical relation between image and object-space straight lines. A build-in self-diagnosis is also integrated in this method, involving the implementation of data snooping statistic test in the process of spatial resection using the Iterated Extended Kalman Filtering (IEKF). The aim of this paper is to present the basic principles of the proposed approach and results based on real data.
Keywords: Automation; Digital photogrammetry; IEKF; Relational matching; Straight lines